Sodium/Na β″ alumina interface: effect of pressure on voids - Spencer Jolly, D; Ning, Z; Darnbrough, JE; Kasemchainan, J; Hartley, GO; Adamson, P; Armstrong, DEJ; Marrow, J; Bruce, PG (American Chemical Society, 2019)
Three-electrode studies coupled with tomographic imaging of the Na/Na-β″-alumina interface reveal that voids form in the Na metal at the interface on stripping and they accumulate on cycling, leading to increasing interfacial current density, dendrite formation on plating, short circuit, and cell failure. The process occurs above a critical current for stripping (CCS) for a given stack pressure, which sets the upper limit on current density that avoids cell failure, in line with results for the Li/solid-electrolyte interface. The pressure required to avoid cell failure varies linearly with current density, indicating that Na creep rather than diffusion per se dominates Na transport to the interface and that significant pressures are required to prevent cell death, >9 MPa at 2.5 mA·cm–2.